TRAUMA, PELARIAN, DAN MARGINALITAS: STUDI WACANA KRITIS NORMAN FAIRCLOUGH ATAS LAGU DIARY DEPRESIKU LAST CHILD - Wahyudi, Teges; Shofiyuddin, Haris (Universitas Islam Zainul Hasan Genggong, 2025)
This article aims to analyze the song's lyrics using the critical discourse approach developed by Norman Fairclough. This analysis focuses on three main dimensions: text dimensions, discursive practices, and social practices. In the text dimension, the lyrics of this song use strong and emotional diction, such as